ANALISIS INDEKS KEBAHAGIAAN DI INDONESIA - B2052162002, Angela.AL (Jurnal Ekonomi Daerah (JEDA), 2019)
Â Â AbstractThis study aimed to examine the effect of economic growth and GRDP per capita on Happiness Index in 33 provinces in Indonesia in 2014 and 2017. The form of this study uses quantitative descriptive. The data source used is secondary data which is data obtained from the National BPS. Data analysis techniques used Multiple Linear Regression in 33 provinces. Statistical data analysis shows: (1) Economic growth has no significant effect on the Happiness Index in Indonesia; (2) Per capita GRDP has a positive and significant effect on the Happiness Index in Indonesia.Â Keyword: economic growth, GDP per capita, and happiness index